2021
DOI: 10.1093/scan/nsab033
|View full text |Cite
|
Sign up to set email alerts
|

Mortality threat mitigates interpersonal competition: an EEG-based hyperscanning study

Abstract: Awareness of death has been shown to influence human cognition and behavior. Yet, how mortality threat impacts our daily social behavior remains elusive. To address this issue, we developed a dyadic experimental model and recruited 86 adults (43 dyads) to complete two computer-based tasks (i.e., competitive and cooperative button-pressing). We manipulated dyads’ awareness of death (mortality threat vs. neutral control, MT vs. NC) and simultaneously measured their neurophysiological activity using electroenceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…Thus, we can interpret that awareness of adjacent individuals, even in the absence of explicit communication, triggers the interpersonal neural synchronization. These findings extend previously reported findings of interpersonal neural synchronization induced by explicit communicative interactions 7 16 and external interactive triggers, such as rhythmic sounds 17 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, we can interpret that awareness of adjacent individuals, even in the absence of explicit communication, triggers the interpersonal neural synchronization. These findings extend previously reported findings of interpersonal neural synchronization induced by explicit communicative interactions 7 16 and external interactive triggers, such as rhythmic sounds 17 .…”
Section: Discussionsupporting
confidence: 91%
“…Recently, hyperscanning techniques using near-infrared spectroscopy (NIRS) or electroencephalography have been widely used for examining the interpersonal synchronization of neural activity 4 6 . Previous studies have focused on explicit communicative group interaction such as cooperation 7 13 and competition 14 16 as the target of hyperscanning. In these studies, fluctuations in interpersonal neural synchronization are observed in a periodic band matching the task interval of repeated trials 8 , 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The common mechanism of interpersonal rapport triggering similar brain activities should be a common theme [27][28][29]. All in all, with the recent literature that suggests the importance of neuron oscillations at specific frequencies [30,31] or decreased gamma-band in the competitive pairs [32], all lend support to the 'communication-through-coherence' hypothesis [33]. Therefore, coherence between two neuronal groups, brain areas, pairs, organizations, societies, or even countries or cultures could be exploited to reach effective communication, benefiting the future of human societies.…”
Section: Discussionmentioning
confidence: 85%
“…A within-dyad bootstrapping analysis was used to control for spurious (i.e., coincidental) BBS (Pérez et al, 2019; Zhou et al, 2021). For each student–student and student–teacher dyad, BBS was computed between all combinations of lectures given at different time points (e.g., Lecture 1–Lecture 2, Lecture 1–Lecture 3).…”
Section: Methodsmentioning
confidence: 99%